(untitled) (Eurasian Journal of Ecology, 2016)
We investigated age-related features of the cardiovascular system in children of school age. We investigated the main hemodynamic parameters: heart rate, systolic and minute volume and blood pressure. According to the results of our studies revealed age and gender indicators physiological characteristics of the cardiovascular system.